Sustained delivery of human growth hormone using a polyelectrolyte complex-loaded thermosensitive polyphosphazene hydrogel - Park, Mi-Ran; Chun, ChangJu; Ahn, Sung-Won; Ki, Min-Hyo; Cho, Chong-Su; Song, Soo-Chang (ELSEVIER, 2010)
A combined system of polyelectrolyte complex (PEC) and injectable, biodegradable and thermosensitive poly(organophosphazene) hydrogel has been suggested as an injectable depot for a controlled and sustained delivery of human growth hormone (hGH) to improve patient compliance. PEC was prepared by mixing polycations with hGH to suppress diffusion of hGH from the hydrogel through an enlargement of the hydrodynamic size of hGH. Among the polycations, poly-L-arginine (PLA) formed a large complex with hGH and its size increased as the amount of PLA increased. When PLA and/or zinc were added to hGH, the time-dependent stability of hGH increased more than that of native-hGH. The polymer solution containing PECs formed a gel at 37 C. PLA decreased the initial release rate of hGH in proportion to the amount of PLA in vitro and in vivo. Zinc increased the released amount of hGH from the PEC-loaded hydrogel in vitro and in vivo. In a pharmacokinetic study in rats, a single administration of PEC-loaded hydrogel resulted in the sustained release of hGH for 5 days. These results suggest that injectable, biodegradable, and thermosensitive PEC-loaded poly(organophosphazene) hydrogel has great potential to be used as an effective delivery system for a sustained release of hGH with improved patient compliance. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: RELEASE FORMULATION; PROTEIN DELIVERY; IN-VIVO; MICROSPHERES; COPOLYMERS; STABILITY; FUSION; GH